Prevalence of depression among secondary level students in Harion Municipality, Sarlahi - Balampaki, Pabitra; Thapa, Janak Kumar; Chaudhjary, Pramodh; Sangroula, Raj Kumar; Shrestha, Arati Dhoju; Pyakurel, Sumitra; Thapa, Salina (International Journal Of Community Medicine And Public Health, 2023)
Background: Depression is a common mental disorder with a depressed mood, loss of interest or pleasure, decreased energy, feelings of guilt or low self-worth, disturbed sleep or appetite, and poor concentration. Globally the prevalence of depression among (15-19 years) males and females are 3.1% and 4.5% respectively. According to WHO, the prevalence of depression in Nepal is 3.2% and the prevalence of depression in (15-19 years) is 7.6%. This research was conducted to determine the prevalence of depression among the secondary-level adolescents of Harion municipality and to examine the variances according to socio-demographic factors, socio-economic factors, etc. Methods: Analytical cross-sectional study design was used in this research. Schools were selected through Simple Random Sampling. Participants were students of 9 and 10 selected schools. The PHQ9 (Patient Health questionnaire) was used to ascertain the prevalence of depression at various levels. Results: Out of 168 students, 97 (57.7%) students had depression. The mean age of the students was 16. Family type of students (p-value=0.036, 95% CI=0.261-0.959 and OR =0.5), students education level (p-value=0.044, 95% CI=0.273-0.986 and OR= 0.519) and physical activities (p-value=0.015, 95% CI=0.248-0.865 and OR=0.463) were found to be statistically significant. Conclusions: The prevalence of depression was seen higher among school-going adolescents in two schools in Harion municipality. There is a need for early identification of depression which can prevent other psychiatric disorders in teen-age.